Information Asymmetry and Religious Seasonality - Abdullah M. Al-Awadhi; Ahmad Bash; Barrak Algharabali; Ibrahim Khatatbeh (Bank Indonesia, 2025)
This paper examines the seasonality in information asymmetry as proxied by the probability of informed trading (PIN) in relation to the Islamic holy month of Ramadan. It utilizes data collected from Boursa Kuwait, covering the period from January 2013 to December 2018, and pooled panel regressions to test the hypothesis that increasing religiosity during Ramadan would reduce the probability of informed trading. The results reveal that the PIN increases during Ramadan relative to other Islamic calendar months, contrary to our hypothesis. Further tests reveal that institutional trading activities increase during Ramadan compared to individual trading. We argue that the presence of sophisticated traders (institutional traders) in the market during Ramadan contributes to the observed increase in the PIN effect. This study contributes to the literature by exploring the relationship between religiosity and information asymmetry in the context of an Islamic financial market, offering new insights into the behaviour of institutional traders during the holy month of Ramadan. We refer this phenomenon as the “Ramadan PIN effect”, which differs from the previously documented